영상정합 기술을 활용한 터널관리시스템의 운영 효율성 제고를 위한 콘텐츠 연구 - 노창균(Chang-gyun Roh); 박범진(Bum-Jin Park); 김지수(Jisoo Kim) (한국콘텐츠학회 논문지, 16(6), 2016)
In South Korea, there are a large number of tunnels because of the mountainous terrain, and to overcome this characteristics, lengths of tunnels are more longer than existing tunnels. The need to improvement current tunnel management contents is giving rise for accidents in tunnel section is continuously increased although lots of efforts to reduce the accidents. Conventionally, disaster prevention have been focused on the Tunnel Management Systems, tunnel operators generally tend to depend on CCTV images for most contents of detailed traffic flow managing. In this paper, investigation about current Tunnel Management Systems contents using IPA survey was conducted, and Priority Improvement Contents(Accident Situation Management Support, 2nd Accident Management Support, Traffic Flow Monitoring), which importance are high, but satisfaction are low, are deducted. Also, CCTV images, lack intuitive understanding, are judged as a main cause of low satisfaction of those contents. To overcome those limitations of the existing Tunnel Management Systems, this study sought to develop a technology for the synthesis of road images to derive traffic information from synthesis images, and the contents improvement stragegy is established. Tunnel operators-oriented satisfaction survey on new contents was carried out, and scored 4.2 on a 5-point scale. This has confirmed that the availability of new contents and at this stage, with pushing ahead of long-tunnels and undersea tunnels construction, politic applications are expected. 한국은 산지가 많은 지형적인 특징으로 터널이 많고, 지형적 특성 극복을 위해 터널의 길이도 점차 장대화되고 있는 중이다. 사고 감소를 위한 노력에도 불구하고 터널내 사고는 지속적으로 증가하고 있어 터널관리시 현 터널관리 콘텐츠의 문제점 및 개선에 대한 필요성이 대두되고 있다. 터널관리시스템은 전통적으로 방재기능 중심으로 운영되고 있어 터널관리자들이 섬세한 교통류를 관리하기 위한 콘텐츠들은 대부분을 CCTV영상에 의존하는 경향이 크다. 이에 본 논문은 IPA 기법을 활용하여 현재의 터널관리시스템 콘텐츠를 조사하여, 중요도는 높으나 만족도는 상대적으로 낮은 중점개선 콘텐츠(돌발상황 관리 지원, 돌발상황 2차사고 관리 지원, 교통류의 모니터링)를 도출하였다. 또한 이들 콘텐츠의 만족도가 떨어지는 이유를 터널관리자를 대상으로 설문조사하여 직관적 이해가 떨어지는 CCTV영상을 원인으로 판단하였다. 도출된 문제점 극복을 위해 영상정합기술을 활용하여 개별 CCTV를 평면화하여 위에서 아래로 내려다 보이는 새로운 영상을 제공하기 위한 시스템을 개발하고, 이를 테스트하여 콘텐츠 개선 전략을 수립하였다. 신규 콘텐츠는 터널관리자를 대상으로 만족도 조사를 재시행 하였으며 5점 만점에 4.2점이 도출되었다. 이를 통해 신규 콘텐츠의 활용성을 확인하였으며, 장대터널의 증가 및 해저터널 건설 등이 추진되고 있는 현 시점에서 정책적 활용이 기대된다.